EXTENDED HÜCKEL ORBITAL FORCES - Eisner,Federico (Sociedad Chilena de Química, 2003)
The forces acting on individual atoms in a molecule, arising from the distorting effect on the molecular framework of the electrons in the different populated molecular orbitals, are calculated within a simple Extended Hückel formalism. The method, which is strongly dependent on the properties of overlap integrals, is applied to the study of several processes and reactions of chemical interest, such as conformational stability of molecules, torsional stability for rotations around a single bond of some simple molecules and the connection between the forces acting upon atoms and the rules derived from conservation of orbital symmetry in concerted reaction. The results show good agreement with the experimental evidence and the known symmetry rules